The Influence of Halal Labeling, Packaging Design, and Product Variations on Consumer Purchasing Decisions of Kanzler Chicken Nuggets at Happy Frozen &; Fresh 2 Kediri - Rossynanda, Dheriska Ima; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2024)
Research Objective: The purpose of this study is to determine the effect of halal labeling, packaging design, and product variations partially and simultaneously on consumer purchasing decisions of Kanzler chicken nuggets in Happy Frozen &; fresh 2 Kediri Design/method/approach: This study uses a quantitative approach with causal research techniques. The population in this study is consumers who have purchased Kanzler chicken nugget products and the sample used in this study was 40 respondents who had made purchases and data collection through observation, questionnaires, interviews, and literature studies. The analysis techniques used are classical assumptions, multiple linear regression, hypothesis tests (T-test and F-test), and determinant coefficients. Research findings: The results of this study are halal labeling, packaging design, and product variations have a partial and simultaneous effect on consumer purchasing decisions for Kanzler chicken nuggets at Happy Frozen & fresh 2 Kediri. Research Limitations: a limitation of this study is the difficulty of retrieving consumer data.